2023
DOI: 10.3390/mi14051049
|View full text |Cite
|
Sign up to set email alerts
|

Natural Convection of Ternary Hybrid Nanofluid in a Differential-Heated Enclosure with Non-Uniform Heating Wall

Abstract: In the field of convective energy transfer, natural convection is one of the most studied phenomena, with applications ranging from heat exchangers and geothermal energy systems to hybrid nanofluids. The aim of this paper is to scrutinize the free convection of a ternary hybrid nanosuspension (Al2O3-Ag-CuO/water ternary hybrid nanofluid) in an enclosure with a linearly warming side border. The ternary hybrid nanosuspension motion and energy transfer have been modelled by partial differential equations (PDEs) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…First, the isolated equation of system (23) for the velocity V is integrated. A seventhorder polynomial is obtained, further substitution of which into the first equation of system (24) (presented below) makes it possible to determine the form of the velocity U as a tenth-order polynomial.…”
Section: Theoremmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the isolated equation of system (23) for the velocity V is integrated. A seventhorder polynomial is obtained, further substitution of which into the first equation of system (24) (presented below) makes it possible to determine the form of the velocity U as a tenth-order polynomial.…”
Section: Theoremmentioning
confidence: 99%
“…It should be noted that the thermal and concentration mechanisms of convection generation are fundamentally different physically. Mathematically speaking, the Oberbeck-Boussinesq equations for thermal convection and concentration convection differ only in dissipative coefficients in the heat conduction equation and in the diffusion equation, respectively [14,[18][19][20][21][22][23][24]. These coefficients differ from each other by several orders of magnitude; therefore, one should expect differences in the structure and evolution of thermal and thermal solution flows.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Bhowmick and Randive [ 33 ] determined that the optimal parameters for maximizing heat transfer and minimizing entropy in a porous wavy channel with non-uniform wall heat flux were 5 mm wavelength and 180° phase angle. Apart from the discussed literature, Faizan et al [ 34 , 35 ] and Rajesh et al [ 36 ] also investigated the impact of NUHF in controlling the heat transfer rate in thermal equipment. These studies demonstrated significant advantages in controlling the heat transfer rate by employing NUHF conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was found that the movement of the hot baffles improved the fluid mixing and resulted in a more effective cooling performance. Rajesh and Sheremet (2023) simulated the natural convection of ternary hybrid nanosuspensions in a cavity with linearly warming side borders. Their analysis highlights that the addition of a third kind of nanomaterial allows for intensifying the energy transport inside the closed chamber.…”
Section: Introductionmentioning
confidence: 99%